2014
DOI: 10.1177/0306624x14548531
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Imprisonment

Abstract: The literature on prison effects is characterised by a focus on negative outcomes. There is a need to acknowledge individual differences. The theme of posttraumatic growth emerged in a subsample of interviews from a study on psychological adjustment in prison. The narratives of this subsample (six female, first-time prisoners) were used to explore the phenomenon of posttraumatic growth during imprisonment. It is argued that the initial shock of incarceration challenged these prisoners' assumptive worlds, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 60 publications
(67 reference statements)
5
47
0
4
Order By: Relevance
“…After scrutinizing databases such as PsycInfo and Google Scholar, we did not find any articles that report on quantitative analysis regarding posttraumatic growth among offenders, except for a few studies focusing on political prisoners and prisoners of war. This is remarkable, particularly because the limited qualitative studies available, as well as some theoretical papers, suggest that both the committed offence and incarceration can challenge the offenders’ global meanings and prompt a profound search for meaning (Braswell & Wells, 2014; Ferrito, Vetere, Adshead, & Moore, 2012; Guse & Hudson, 2014; Mapham & Hefferon, 2012; Maruna, Wilson, & Curran, 2006; Ronel & Elisha, 2011; Ronel & Segev, 2014; van Ginneken, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After scrutinizing databases such as PsycInfo and Google Scholar, we did not find any articles that report on quantitative analysis regarding posttraumatic growth among offenders, except for a few studies focusing on political prisoners and prisoners of war. This is remarkable, particularly because the limited qualitative studies available, as well as some theoretical papers, suggest that both the committed offence and incarceration can challenge the offenders’ global meanings and prompt a profound search for meaning (Braswell & Wells, 2014; Ferrito, Vetere, Adshead, & Moore, 2012; Guse & Hudson, 2014; Mapham & Hefferon, 2012; Maruna, Wilson, & Curran, 2006; Ronel & Elisha, 2011; Ronel & Segev, 2014; van Ginneken, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In van Ginnenken’s (2014) study, six female prisoners were interviewed about their current prison experience. They each experienced posttraumatic growth after coping with the initial entry shock of being imprisoned.…”
Section: Introductionmentioning
confidence: 99%
“…Elles montrent que des mécanismes complexes entrent en jeu durant ces phases, marquées par des perturbations dans la vie quotidienne, la perte de repères et une grande ambivalence (voir Healy, 2012 ;King, 2014). Cette phase peut même constituer un facteur de risque de victimisation pour les personnes incarcérées (Stevens, 2012 ;van Ginneken, 2016 ;Vanhooren, Leijssen et Dezutter, 2017). Ainsi, pour les justiciables, retourner à ses anciennes habitudes peut paraître moins difficile que de se désister (Halsey et al, 2017 ;Healy, 2012 ;King, 2014).…”
Section: L'assistance Formelle Dans Les Phases Initiales Du Désistementunclassified
“…(Healy, 2012, p. 388) L'assistance formelle au carrefour des changements cognitifs et identitaires Éventuellement, la plupart des désisteurs en devenir se retrouvent entre deux mondes : ils ne se perçoivent pas comme des citoyens ni comme des contrevenants (F. -Dufour et Brassard, 2014). L'aide formelle gagnerait donc à mettre l'accent sur la (re)construction des scripts narratifs afin de faciliter cette transition d'un monde à l'autre (Blagden et al, 2016 ;F.-Dufour et Brassard, 2014 ;Halsey et al, 2017 ;Harris, 2014 ;Panuccio et al, 2012 ;Radcliffe et Hunter, 2016 ;Ricciardelli, 2018 ;Stevens, 2012 ;van Ginneken, 2016 ;Vanhooren et al, 2017) :…”
Section: La Mise En Scène Du Changementunclassified
“…Upon imprisonment, individuals experience various forms of deprivation. Sykes' (1958) study found that incarcerated men faced particular hardships, such as separation from loved ones, deprivation of needed resources, and loss of freedom. Living in confinement with antisocial others and supervision by antagonistic staff presents substantial barriers to developing a prosocial future life script and ultimately desisting from crime (Irwin & Owen, 2005).…”
Section: The Pains Of Imprisonmentmentioning
confidence: 99%